(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Inpost- independence India, in order to facilitate improvements in agriculturalproduction and attain food self – sufficiency, the stance of policy was toensure sufficient and timely credit at “reasonable” rates of interest to aslarge a segment of the rural population as possible. The strategy to achievethis was threefold: expansion of the institutional base, directed ending todisadvantage borrowers, and credit provision at concessional rates of interest.The latter was justified in terms of the perceived mismatch between the longer term returns offarm investment in relation to cultivator households ‘ short term consumptionneeds and requirements to service the loans.